Thermal Diffusivity and Electrical Conductivity Studies of Polyaniline Based Materials and Selected Ceramics - Liew, Josephine Ying Chyi (2003)
In this work, the photoflash and four-point probe techniques were respectively applied for thermal diffusivity and electrical conductivity measurement on polyaniline, polyaniline blends, polyaniline composite and ceramic at room temperature. In the photoflash technique, the signal was initially generated by a high intensity camera flash as an excitation source. A fast response K -type thermocouple was used as a detector to monitor the temperature at the rear surface of the sample. The photoflash signal was captured as a function of time and the half rise time; t₀.₅ of each sample was then analyzed to determine the thermal diffusivity. The photoflash setup was first calibrated with the sample of known thermal diffusivity. The results indicate that the thermal diffusivity of the calibration sample correlated well with the results from literature.